Canines make the difference: a new species of Hypsugo (Chiroptera: Vespertilionidae) from Laos and Vietnam - Görföl, Tamás; Csorba, Gábor; Eger, Judith L.; Son, Nguyen Truong; Francis, Charles M. (Zootaxa, 2014)
Hypsugo was regarded as a subgenus of Pipistrellus by many authors, but its generic distinctiveness is now widely accepted. According to recent taxonomic arrangements, nine species are known to occur in Southeast Asia. During the investigation of material recently collected from Lao PDR and Vietnam we identified an additional species and hence describe it here as Hypsugo dolichodon n. sp. It resembles H. pulveratus, but is larger with conspicuously long canines and differs considerably in the DNA barcode gene sequence.